Analysis of the Correlation Between Layout and Wayfinding Decisions in Hospitals - Esra Aksoy; Dicle Aydın; Gökhan İskifoğlu (Megaron, 2020)
As a research topic of several disciplines such as psychology, sociology, and especially architecture, wayfinding is always on the agenda and is open to research. In this paper, the relationships between the wayfinding decisions of the users in hospitals and the layout of the hospitals were examined on inexperienced users. Hospitals, which are places where people frequently visit and compete over time to gain their health during their visits, are public spaces with the highest circulation of users during the day. For this reason, hospitals were preferred as research areas. Factors affecting the spatial perception of the users during wayfinding were tested in the real space scene. The relationship between wayfinding decisions of users and the layout of the hospital was analyzed by VGA over GoPro camera according to the selected routes. The wayfinding behavior analysis of the users was conducted with the GoPro camera. In addition, the VGA of the plans consisting of routes was performed with Depthmap software. Finally, the numerical data obtained from both analyzes were interpreted using the SPSS 24 statistical package and appropriate digital analysis. As a result of the analysis, it was revealed that the layout of a hospital is effective in the wayfinding decisions of the users due to several spatial variables, and the layout and the wayfinding behavior are closely related.